Warburg-Cinotti disease variant p.Tyr740Cys enhances catalytic activity of DDR2 kinase - Ziteng Hao; Birgit Leitinger (PLoS ONE, 2025)
The discoidin domain receptor DDR2 is a collagen-binding receptor tyrosine kinase whose dysregulation is associated with a wide range of diseases. Missense mutations in the DDR2 kinase domain cause Warburg-Cinotti syndrome in an autosomal dominant manner. Warburg-Cinotti syndrome is a severe connective tissue disorder, characterised by a range of manifestations including joint contractures of the hand, corneal vascularisation and pannus, skin fusion and infection, keloid plaques and acro-osteolysis. The Warburg-Cinotti variants, p.Leu610Pro and p.Tyr740Cys, were previously hypothesised to cause disease through a gain-of-function mechanism but mechanistic studies addressing this notion have been lacking. Here we show that both disease variants exhibit ligand-independent constitutive autophosphorylation when expressed as full-length proteins in mammalian cells. We also characterised the enzyme kinetics of soluble WT and DDR2-Y740C kinase constructs. WT DDR2 kinase was found to follow the same two-step activation mechanism previously characterised for DDR1 kinase but with enhanced autophosphorylation and substrate phosphorylation rates. Compared with WT DDR2, DDR2-Y740C displayed further enhanced autophosphorylation and substrate phosphorylation rates, but no effect on ATP binding affinity. The increased catalytic rates of unphosphorylated DDR2-Y740C kinase were similar to those of fully phosphorylated WT DDR2, indicating that the missense variant bypasses all autoinhibitory constraints and adopts the fully active kinase conformation. Tyrosine-740 is a residue in the A-loop of DDR2 kinase that forms autoinhibitory hydrogen bonds with key catalytic residues. These hydrogen bonds cannot form in the cysteine-substituted variant, providing a structural explanation for the release of the A-loop from its autoinhibitory conformation.